Uncorrelated electron-hole transition Energy in GaN│InGaN│GaN Spherical QDQW Nanoparticles - El Ghazi, Haddou; Jorio, Anouar; Zorkani, Izeddine (Communications in Physics, 2013)
The electron (hole) energy and uncorrelated \(1S_e - 1S_h\) electron-hole transition in Core(GaN)| well(In\(_x\)Ga\(_1 - x\)N)| shell(GaN) spherical QDQW nanoparticles is investigated as a function of the inner and the outer radii. The calculations are performed within the framework of the effective-mass approximation and the finite parabolic potential confinement barrier in which two confined parameters are taking account. The Indium composition effect is also investigated. A critical value of the outer and the inner ratio is obtained which constitutes the turning point of two indium composition behaviors.